The Effect of Competence and Coordination on Employee Performance with Motivation as Intervening Variable in Regional Tax and Levy Management Agency of Musi Rawas Regency - Yohanes Susanto; Muhammad Effendi; Suryana Agam (Program Studi Magister Manajemen FE Unsri, 2022)
ABSTRACT Research objective – This study aims to determine the effect of competence and coordination on employee performance with motivation as an intervening variable at the Regional Tax and Levy Management Agency of Musi Rawas Regency. Design/Methodology/Approach – In this study, the census method was used by giving questionnaires to the entire population of 105 people. Structural equation modeling (SEM) analysis was used for data analysis which is operated through the LISREL 8.70 program. Findings – The results showed that the competence and coordination variables each had a significant positive effect on employee motivation and performance. In addition, motivation as an intervening variable shows an insignificant positive effect on employee performance. Research Limitations – This work is only applicable to the employees at Regional Tax and Levy Management Agency of Musi Rawas Regency. Originality/value – This is the first study that investigates the impact of competence and coordination on employee performance with motivation as intervening variable at Regional Tax and Levy Management Agency of Musi Rawas Regency.